Removal of Diclofenac from Contaminated Water using Organoclay as Reactive Material - Saadoon, Sara; Mohammed, Alaa Kareem; Rashid, Israa M.; Isahak, Wan Nor Roslam Wan; Rahimnejad, M. (Al-Khwarizmi Engineering Journal, 2024)
This study is concerned with the adsorption of Diclofenac (DIC) from polluted water using modified bentonite. Hexadecyl trimethyl ammonium bromide (HTAB) was used to alter the hydrophilic nature of the bentonite to a hydrophobic one. Various effecting parameters were investigated such as: contact time, pH, agitation rate, adsorption dosage,acidity pH, mixing time time, and initial adsorbate concentration (Co). The best result obtained for the removal of Diclofenac is 98% which  occurred at 30 ppm initial concentration, acidity pH 7, 100 min mixing time, and o.3g/100ml (DIC) dosage. Langmuir isotherm model eas found the more suitable model to represent the adsorption process.On examining the kinetics of the adsorption process, the pseudo-second-order kinetic model well describes the experimental data. Finally, thermodynamic investigations show that the adsorption process is endothermic, spontaneous as well as exhibited characteristics of physisorption.